Realizacja charyzmatu trynitarskiego w Polsce - Kowalski, Maciej J. (2022)
REALISATION OF TRINITARIAN CHARISM IN POLANDThe publication presents the ways of realisation of Trinitarian charism in Poland on the basis of analysis of Church documents concerning charism and the basic elements of Trinitarian charism. The research also included source material on the history and symptoms of Trinitarian charism, including in particular documents testifying to the history and activity of Trinitarians in Poland. In the treatise, the following methods have been used: analytical, historical and comparative. Furthermore, the author’s considerations are divided into four chapters. In the first chapter, the notion of monastic life charism as well as the genesis and development of Trinitarian charism, especially in Polish lands, have been discussed. The next three chapters present two essential elements of Trinitarian charism, i.e. the worship of the Holy Trinity and the service of redemption and mercy, as well as the idea of a community based on equality and brotherhood, in which this charism is manifested. According to the accepted methodology, a starting point for these considerations included each time a reference to the teachings of the Church on a given subject, and later the discussion concerned the development of particular elements of Trinitarian charism over the centuries was presented. The forms of their realisation in Poland are discussed as well.